Distribusi neuron serotonergik pada hipokampus Lasiwen (Myotis sp) sebagai satwa liar yang berpotensi menjadi reservoir virus rabies - Tri Wahyu Pangestiningsih; Ariana Ariana; Irma Padeta; Arvendi Rahma Jadi; Woro Danur Wendo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Myotis sp is an Indonesian microchiropteran, insectivore bat that potential to be a reservoir for rabies virus. Rabies is fatal viral encephalitis and bat could act as wildlife potential reservoirs for the rabies virus and can transmit the disease to humans as the zoonotic disease. Hippocampus is one of diagnostic tissue for rabies disease and serotonergic neuron could involved in pathogenesis of rabies disease. The aim of the study is to investigate the distribution of serotonergic neurons in Myotis sp hippocampus. Five Myotis sp. were captured from wild population in Central Java, and were humanly anesthetized using ketamine and xylazin. The animals were perfused intracardially using NaCl 0.9% as the pre-rinse followed by 10% formaldehyde to fix it. The cerebrums were collected and processing the for paraffin embedding. Cerebrums were sectioning in saggital sections, 12 µm thickness serially with 120 µm intervals. The tissues were staining immunohistochemistry using antibody to serotonin (1/300; Bioss, Cat. No: bs-1126R) 2 night incubation in 4 oC temperature. The solution for blocking background, secondary antibody, avidin-biotin-peroxidae complex and chromogen using kit Starr Trek Universal HRP Detection System (Biocare Medical, Cat No: STUHRP700) and were analyzed descriptivelly. The results show that serotonergic neuros were distributed in the all area of the of Myotis sp hippocampus. In dentate gyrus neuron serotonergic (Sert-IR)s are round in shape and mostly distributed in the middle layer, few in the superficially also deeper layers. In the hippocampus , the Sert-IR neurons are pyramidal in shape and distributed in the CA1, Ca2 and CA3 areas. In subiculum, the Sert-IR neurons are pyramidal in shape, more wider distributed than in the CA1 with no differences between outer layer and deeper layer. The conclutions of this research are the serotonergic neurons are distributed in the all area of hippocampus